Avogadro constant measurements using enriched 28Si monocrystals. (12th December 2017) - Fujii, K; Massa, E; Bettin, H; Kuramoto, N; Mana, G
Abstract: Since 2011, the International Avogadro Coordination has been measuring the Avogadro constant by counting the atoms in enriched 28 Si monocrystals. This communication provides guidance on how the recently published results should be used to update the values of the Avogadro constant measured so far.